SISTEM PENUNJANG KEPUTUSAN PEMILIHAN MAKANAN PADA PENDERITA MAAG MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX (CPI) - Apri Liandri; Yolen Perdana Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The rapid advancement of technology has significantly impacted various aspects of life, including the field of healthcare. Decision support systems have emerged as a solution to aid humans in problem- solving and acquiring relevant information. In this context, this research aims to implement the Composite Performance Index (CPI) method as a decision support system for food selection in patients with gastric ulcers. Regular eating patterns are crucial for maintaining bodily health, whereas irregular eating patterns can lead to digestive disorders, particularly in the stomach or gastric region. If left unaddressed, gastric ulcers can worsen and cause recurring discomfort, ultimately affecting daily activities. Food plays a vital role in providing essential nutrients such as carbohydrates, fats, and proteins. This research employs the Composite Performance Index (CPI) method as an approach to select appropriate foods for gastric ulcer patients. CPI utilizes a composite index to evaluate food alternatives based on relevant criteria. The objective of this study is to develop an application using the CPI model to assist gastric ulcer patients in choosing suitable foods, preventing recurrences, and improving their quality of life. By conducting this research, it is anticipated that a decision-making application based on the CPI method can be developed. This application will aid gastric ulcer patients in selecting foods tailored to their condition, thus preventing potential recurrences and enhancing their overall well-being. Therefore, this research holds significant potential in the management of gastric ulcers through the implementation of a decision support system.